1982
DOI: 10.1111/j.1432-1033.1982.tb05803.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary Structure of the Glycans from Human Lactotransferrin

Abstract: The polypeptide chain of human lactotransferrin possesses two glycosylation sites to which glycans are linked through an N-(P-asparty1)-N-acetylglucosaminylamine bond and which are structurally heterogenous. After chymotryptic or pronase digestions, glycopeptides with five different glycan structures could be isolated. For three of them, the structure has been determined by the application of methanolysis, methylation analysis, hydrazinolysis/nitrous deamination, enzymatic cleavage and 'H-NMR spectroscopy at 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
114
0

Year Published

1984
1984
2004
2004

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 199 publications
(126 citation statements)
references
References 43 publications
12
114
0
Order By: Relevance
“…Because casein synthesis is not initiated in the first few days of lactation (Kunz & Lönnerdal, 1990), whey proteins make the largest contribution to total protein at the beginning of lactation, particularly secretory IgA (which contains 12% carbohydrate) and lactoferrin (6% carbohydrate) (Kunz & Lönnerdal, 1990;Rudloff & Kunz, 1997). The carbohydrate side chains of human lactoferrin consist of an N-acetyl-lactosamine glycan with sialic acid in the terminal position (Spik et al, 1982). Cow's milk, however, is low in lactoferrin and the glycan side chains show pronounced differences to human lactoferrin.…”
Section: Gm1 Long-term (Several Weeks)mentioning
confidence: 99%
“…Because casein synthesis is not initiated in the first few days of lactation (Kunz & Lönnerdal, 1990), whey proteins make the largest contribution to total protein at the beginning of lactation, particularly secretory IgA (which contains 12% carbohydrate) and lactoferrin (6% carbohydrate) (Kunz & Lönnerdal, 1990;Rudloff & Kunz, 1997). The carbohydrate side chains of human lactoferrin consist of an N-acetyl-lactosamine glycan with sialic acid in the terminal position (Spik et al, 1982). Cow's milk, however, is low in lactoferrin and the glycan side chains show pronounced differences to human lactoferrin.…”
Section: Gm1 Long-term (Several Weeks)mentioning
confidence: 99%
“…However, these glycoproteins differ in the number, the structure and the location of their glycans [9][10][11][12]. Otherwise, these transferrins bind to different cells such as reticulocytes (serotransferrin) [131, enterocytes (lactotransferrin) [14,15] and chick embryo red blood cells (ovotransferrin) [16], thus suggesting that specific transferrin receptors are present at the surface of these cells and recognize a glycan, a peculiar region of the polypeptide chain, or both.…”
Section: Introductionmentioning
confidence: 99%
“…Major progress has been made in the determination of its glycan [6] and peptide [7,8] sequences, three-dimensional structure and the understanding of iron capture [9, 101. In contrast, little is known about either its biological activity or target cells.…”
mentioning
confidence: 99%
“…Lactotransfemn (also called lactoferrin), discovered by Montreuil et al in human milk [l, 21 was also found in human granulocytes [3] and numerous epithelial secretions [4, 51. Major progress has been made in the determination of its glycan [6] and peptide [7,8] sequences, three-dimensional structure and the understanding of iron capture [9, 101. In contrast, little is known about either its biological activity or target cells.…”
mentioning
confidence: 99%